Estimating the Size of Sailfin Catfish (Pterigoplichthys sp) at First Gonad Maturity in Sidenreng Lake, South Sulawesi, Indonesia - Permatasari, Devi; Hasrianti, Hasrianti; Damis, Damis; Putri, Rini Sahni (Politeknik Kelautan dan Perikanan Sorong, 2025)
The invasion of the sailfin catfish (Pterygoplichthys sp.) in Lake Sidenreng has caused serious ecological disruption and threatens the sustainability of local fishery resources that support the livelihoods of surrounding communities. This study aimed to analyze the reproductive aspects of female sailfin catfish as a basis for population control efforts, by estimating the fork length at first gonadal maturity (Lm₅₀) and calculating the gonadosomatic index (GSI). A total of 164 female sailfin catfish were collected using gill nets from various sampling sites and analyzed at the Basic Laboratory of the Faculty of Science and Technology. GSI analysis showed values ranging from 0.28% to 15.09%, with an average of 4.29%. Most individuals were found at gonadal maturity stage IV, indicating a high reproductive readiness. The estimated Lm₅₀ was 214.12 mm, suggesting that these fish are capable of reproducing at a relatively small body size. These findings reveal a high reproductive potential, which may accelerate the invasion rate of this species in Lake Sidenreng. Information on reproductive characteristics is essential as a foundation for formulating management strategies to suppress population growth and support the sustainability of the aquatic ecosystem.